2017
DOI: 10.1007/s10900-017-0447-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus Genotypes and Abnormal Pap Smears Among Women in the Military Health System

Abstract: Human papillomavirus infection (HPV) is the most common sexually transmitted infection among United States Military Servicemembers, and present in the majority of cervical cancers. Many of these infections are preventable, but HPV immunization is not mandatory during military service. The objective of this study was to examine the prevalence of vaccine-preventable cervical disease among women enrolled in the San Antonio Military Health System. This is a retrospective cross-sectional study of Pap smear results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This multiplex real-time PCR-based method targets the L1 region of the viral genome and allows simultaneous genotyping of 28 HPV types and an internal control. Two PCR reactions were performed for each sample to detect the 19 HR HPV types (HPV 16,18,26,31,33,35,39,45,51,52,53,56,58,59, 66, 68, 69, 73, 82) and the 9 LR HPV types (HPV 6,11,40,42,43,44,54,61,70). Negative and positive controls were included in all PCR runs.…”
Section: Specimen Collection and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…This multiplex real-time PCR-based method targets the L1 region of the viral genome and allows simultaneous genotyping of 28 HPV types and an internal control. Two PCR reactions were performed for each sample to detect the 19 HR HPV types (HPV 16,18,26,31,33,35,39,45,51,52,53,56,58,59, 66, 68, 69, 73, 82) and the 9 LR HPV types (HPV 6,11,40,42,43,44,54,61,70). Negative and positive controls were included in all PCR runs.…”
Section: Specimen Collection and Processingmentioning
confidence: 99%
“…However, data show that the prevalence of STIs is still higher compared with the general population. [9][10][11] The prevalence of the STIs in the army is not only dependent on the military environment, but it is also influenced by the STI status of members joining the military service.…”
Section: Introductionmentioning
confidence: 99%
“…Alarmingly, HPV infection, as well as HPV-related cervical dysplasia, are more common among ADSM than in the general US population, putting ADSM at an even greater risk for cervical cancer. ( Agan et al, 2013 Feb , Daly et al, 2018 ) There is very limited information regarding why HPV and cervical dysplasia are more common among ADSM; however, researchers have speculated that ADSM may be more likely to engage in risk-taking, which may influence STI incidence. ( Agan et al, 2013 Feb ) Other researchers have suggested that rates may be higher among ADSM due to greater access to STI testing among military populations.…”
Section: Introductionmentioning
confidence: 99%